The highest limiting Z in the extended periodic table. (17th November 2015) - Gambhir, Y K; Bhagwat, A; Gupta, M
Abstract: The problem of finding the highest limiting Z in the extended periodic table is discussed. The upper limit suggested by the atomic many body theory at Z  = 172 may be reached much earlier due to nuclear instabilities. Therefore, an extensive set of calculations based on the relativistic mean field formulation are carried out for the ground state properties of nuclei with Z  = 100 to 180 and N / Z ratio ranging from 1.19 to 2.70. This choice of Z and N extends far beyond the corresponding values of all the known heavy to superheavy elements. To facilitate the analysis of the huge quantity of calculated results, various filters depending upon the pairing energies, one and two nucleon separation energies, binding energy per particle ( BE / A ) and α -decay plus fission half lives, are introduced. The limiting value of Z is found to be 146. For the specific filter with 5.5 MeV a few nuclei with Z  = 180 also appear. No evidence for the limiting Z value 172 is found. We stress the need to bridge the atomic and nuclear findings and to arrive at an acceptable limiting value of highest Z (or rather combination of Z and N ) of the extended periodic table.